Контрасећање левице: начела - Todor Kuljić (Токови историје, 2021)
The paper considers some principles of left-wing memory culture after 1989. How should the left remember its own past? It should define its own perception of time and its memory priorities. In dialectical memory one should remember historical antitheses. In the past, one needs to recognize the stronger or weaker internal tensions of certain time segments, not the glorious contents of one’s own past. In the interwar years, the left introduced a new organization of time. This paper views the evolution of the left-wing’s philosophy of history and gives a new definition of the relationship between past and present. It points out the defeated left's gnoseological advantage. Unlike the identity-based linear view of one's own glorious ethnic past, the framework of the left-wing's self-reflexive memory is temporal contingency. It contains the dialectical balance of the contradictions characteristic for the left-wing’s past.